2013
DOI: 10.1002/ange.201307718
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Platinum Anticancer Drugs by Human Copper ATPases ATP7A and ATP7B

Abstract: Cisplatin, carboplatin, and oxaliplatin are widely used anticancer drugs. Their efficacy is strongly reduced by development of cell resistance, a phenomenon not entirely understood, with contribution of drug detoxification, defective accumulation, and efflux from the cell. Downregulation of CTR1, responsible for Cu uptake by the cell, and up-regulation of the Cu-ATPases, ATP7A and ATP7B, which accept Cu from the cytosolic chaperone Atox1 and transfer the metal ion into the secretory pathway where it is incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…ATP7A mediates the transport of platinum drugs across the cellular membranes, and is considered to sequester platinum agents in intracellular compartments and to prevent their reaction with nuclear DNA [24,25]. A correlation between the expression of ATP7A and the degree of acquired resistance to platinum drug in cultured cells and tumor samples suggests that the copper transporters are important constituents of the program that regulates sensitivity to platinum drugs [26,27]. ATP7A C2299G, mutated in high frequency of 23.2 % in Chinese population, can change the gene functions.…”
Section: Discussionmentioning
confidence: 99%
“…ATP7A mediates the transport of platinum drugs across the cellular membranes, and is considered to sequester platinum agents in intracellular compartments and to prevent their reaction with nuclear DNA [24,25]. A correlation between the expression of ATP7A and the degree of acquired resistance to platinum drug in cultured cells and tumor samples suggests that the copper transporters are important constituents of the program that regulates sensitivity to platinum drugs [26,27]. ATP7A C2299G, mutated in high frequency of 23.2 % in Chinese population, can change the gene functions.…”
Section: Discussionmentioning
confidence: 99%
“…All MBDs of these ATPases share a high sequence homology and exhibit similar protein folding with a conserved Cu I ‐binding motif CXXC . In addition, all of the MBDs show similar binding affinity to cuprous ion .…”
Section: Figurementioning
confidence: 96%
“…It has been reported that pre‐loading with Cu can enhance the platination of copper chaperones Atox1 and Cox17, in spite of the fact that Pt II and Cu I bind to the same coordination site . In order to investigate the effect of Cu I on the platination of these ATPases, the reaction with cisplatin was conducted on Cu‐loaded proteins.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations